2019
DOI: 10.1111/ijfs.14274
|View full text |Cite
|
Sign up to set email alerts
|

The effect of in vitro gastrointestinal simulation on bioactivities of kefir

Abstract: Kefir is a fermented milk beverage and known to have positive effects on gut microbial diversity and human health. In this study, digested and undigested kefir samples were compared for changes in their antihypertensive, antidiabetic, antioxidant and antimicrobial activities. Results showed that the amount of total phenolic substances, 2,2-diphenyl-1-picrylhydrazyl radical scavenging (DPPH) activity, and the angiotensin-converting enzyme inhibitor (ACE-I) activity increased from 43.76 AE 0.005 mg gallic acid e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The consumption of kefir has been reported to positively impact the gut microbiota and overall condition of the digestive system [33,[76][77][78]. Additionally, an in vitro study suggests that kefir's passage through the human gastrointestinal tract, and its consequent digestion, can improve its nutritional profile and bioactivity [79]. However, to date, most studies aiming to establish the benefits to human health of kefir consumption have been based in animal models, or in cell culture systems wherein the digestion of kefir does not occur, thus providing limited information [28,79].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consumption of kefir has been reported to positively impact the gut microbiota and overall condition of the digestive system [33,[76][77][78]. Additionally, an in vitro study suggests that kefir's passage through the human gastrointestinal tract, and its consequent digestion, can improve its nutritional profile and bioactivity [79]. However, to date, most studies aiming to establish the benefits to human health of kefir consumption have been based in animal models, or in cell culture systems wherein the digestion of kefir does not occur, thus providing limited information [28,79].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an in vitro study suggests that kefir's passage through the human gastrointestinal tract, and its consequent digestion, can improve its nutritional profile and bioactivity [79]. However, to date, most studies aiming to establish the benefits to human health of kefir consumption have been based in animal models, or in cell culture systems wherein the digestion of kefir does not occur, thus providing limited information [28,79]. Of note, none of the in vivo human studies found in the literature observed the skin impact of a diet containing traditionally homemade kefir as the probiotic, neither in healthy nor atopic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the titratable acidity of traditional kefir was found to be 0.71% (Üstün‐Aytekin et al, 2020). According to Codex Alimentarius, the minimum titratable acidity of kefir is 0.6% (expressed as a percentage of lactic acid) (Codex Standard, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The dairy industry provides the most popular probiotic-containing beverages due to the effective transport of live probiotics [89][90][91][92], which can be associated with various health-promoting effects [93][94][95][96][97][98][99][100][101][102][103][104]. In a study by Cordeiro et al [105] a mouse model of infection control caused by Salmonella typhimurium, showed that conventional fermented dairy beverages had a protective effect against pathogenic bacteria.…”
Section: Non-dairy In Vitro Blueberry Beverages Controlled Retinal Pimentioning
confidence: 99%